1978
DOI: 10.1103/revmodphys.50.181
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanics-The key to understanding magnetism

Abstract: The existence of magnetic materials has been known almost since prehistoric times, but only in the 20th century has it been understood how and why the magnetic susceptibility is influenced by chemical composition or crystallographic structure. In the 19th century the pioneer work of Oersted, Ampere, Faraday and Joseph Henry revealed the intimate connection between electricity and magnetism. Maxwell's classical field equations paved the way for the wireless telegraph and the radio. At the turn of the present ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…(4)] was not null. In this interpretation, the susceptibility is independent of the temperature, because h 2 i T is roughly proportional to T. This is different from the case discussed by Van Vleck where the susceptibility is independent of the temperature when the energy distances E between the ground state and the excited states are large as compared to kT [14,17]. Corrections to the susceptibility due to the distortion of the molecule have already been observed for simple polar molecules but, in most systems, these distortions induce small corrections to the dipole and the dominant term in the susceptibility remains proportional to 1=T [13,18].…”
mentioning
confidence: 80%
“…(4)] was not null. In this interpretation, the susceptibility is independent of the temperature, because h 2 i T is roughly proportional to T. This is different from the case discussed by Van Vleck where the susceptibility is independent of the temperature when the energy distances E between the ground state and the excited states are large as compared to kT [14,17]. Corrections to the susceptibility due to the distortion of the molecule have already been observed for simple polar molecules but, in most systems, these distortions induce small corrections to the dipole and the dominant term in the susceptibility remains proportional to 1=T [13,18].…”
mentioning
confidence: 80%
“…2 Their work suggested that the 4f electrons responsible for the magnetism of the rare earth are sequestered in the interior of the atom, and so experience only a small crystalline field. 3 Thus, they explained why Hund's rule with L-S coupling could give values of the magnetic moments of rare-earth ions very close to experimental observations, at least in the high-temperature region. However, understanding the magnetic ordering of the rare earths is still a challenging problem to the magnetists.…”
Section: Introductionmentioning
confidence: 98%
“…Magnetic properties of a system containing magnetic ions are related to its electronic structure, [1][2][3][4] and are commonly probed by measuring the temperature-dependence of its magnetic susceptibility χ(T) at a given magnetic field, the field-dependence of its magnetization M(H) at a very low temperature, or the magnetic specific heat as a function of temperature. When fitted with a Curie-Weiss law, the paramagnetic region of the χ(T) vs. T plot leads to the CurieWeiss temperature θ and the effective magnetic moment μ eff .…”
mentioning
confidence: 99%